Dynamic Simple Syndication (DSS) - Beltran Romero, Laidy Teresa; Gualtero Martinez, Rodrigo Humberto; Gaitán Naranjo, Holmer Alexander (Escuela Colombiana de Ingeniería Julio Garavito, 2015)
The technology has reached such a point that through the network information can be shared in a very simple way, files have been created that follow a certain standard when they are sent, in such a way that they can be interpreted by an infinity of applications; These files are known as RSS that are based on an XML standard. It is for this reason that in this project we sought to create an application that allows us to obtain, process and transform these RSS files specifically for news to show information in real time that will be used in massive information dissemination environments. What really differentiates this application is that it can be executed in a device called Raspberry Pi that is not only cheaper, but will replace the computers that are normally used for this type of applications.

La tecnología ha llegado a tal punto en que a través de la red se puede compartir información de manera muy simple, se han creado archivos que siguen un cierto estándar al momento de enviarse, de tal forma que pueden ser interpretados por una infinidad de aplicaciones; estos archivos se conocen como RSS que se basan en un estándar xml. Es por esta razón que en este proyecto se buscó crear una aplicación que permita obtener, tratar y transformar estos archivos RSS específicamente de noticias para mostrar información en tiempo real que se utilizará en ambientes de divulgación masiva de información. Lo que realmente diferenciará esta aplicación es que podrá ser ejecutada en un dispositivo llamado Raspberry Pi que no solamente es más económico, sino que remplazará a los computadores que normalmente se utilizan para este tipo de aplicaciones.
Keywords: Administración de la Información; Information Management